Genetic polymorphisms of adhesion molecules and kidney transplant survival - Heinold, Andreas; Opelz, Gerhard; Döhler, Bernd; Scherer, Sabine; Ruhenstroth, Andrea; Tran, Thuong Hien (Transplantation, 2010)
BACKGROUND.: Adhesion molecules play a key role in the recruitment of leukocytes to sites of inflammation. Genetic polymorphisms of adhesion molecules may alter their expression or function and may thereby influence the process of leukocyte infiltration in the transplanted organ. It has also been suggested that polymorphic adhesion molecules may act as minor histocompatibility antigens. METHODS.: In two randomly selected cohorts (954 and 1002 kidney transplants), the effect of L-selectin/CD62L (codon 206 and 213), platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31; codon 125, 563, and 670), and activated leukocyte cell adhesion molecule (ALCAM/CD166; codon 258) single nucleotide polymorphisms on 5-yr allograft survival was investigated. DNA samples and clinical data were provided by the Collaborative Transplant Study. Recipients and donors were genotyped by polymerase chain reaction sequence-specific primer. A multivariate analysis was performed using a Cox regression model. RESULTS.: Incompatibility for L-selectin at codon 213 was significantly associated with better graft survival in the first cohort, but the effect could not be replicated in the second cohort. Polymorphisms of PECAM-1 and ALCAM had no impact on graft outcome. CONCLUSIONS.: This is the first comprehensive and large-scale study on the relevance of L-selectin, PECAM-1, and ALCAM genetic polymorphisms in kidney transplantation, showing no significant associations of recipient or donor genotypes with allograft survival. Because the effect of L-selectin mismatch was not reproducible, a putative role of adhesion molecules as minor histocompatibility antigens cannot be confirmed. Our results demonstrate the importance of testing large sample sizes and of performing confirmation studies to validate genetic associations.